MIXED MARRIAGE: A PASTORAL CHALLENGE TO THE FAMILY - Payyappilly, Sebastian (Asian Horizons, 2014)
This study is made in the light of the Preparatory Document of the Extraordinary Synod of Bishops, “Pastoral Challenges to the Family in the Context of Evangelization.” The Document highlights the concern of the Church over certain widespread practices of the society today which have been corroding the fundamental Christian principles and the essential family values. Though many of the social practices identified by the Church are to be remedied for the sake of the preservation of faith and family life through proper pastoral care, there is no onetime definitive solution possible to this effect. This study focuses on pastoral care of the mixed marriage families in strict sense, which means, the marriages between a Catholic and a baptized person who is not in full communion with the Catholic Church. Mixed marriage is not a new development. In the modern society, because of the revolutionized social and religious consciousness, people are questioning age-old values, including marriage and family life. More and more young people challenge the very custom and relevance of getting married within one’s own ethnic or religious community. The Catholic Church has been always cognizant in safeguarding certain values, namely, the faith of the members, the education of children, and the unity of faith and harmony within the family.